Functionalized CdSe/ZnS QDs for the Detection of Nitroaromatic or RDX Explosives - Freeman, Ronit; Finder, Tali; Bahshi, Lily; Gill, Ron; Willner, Itamar (Advanced materials (Weinheim), 2012)
Chemically modified CdSe/ZnS quantum dots (QDs) are used as fluorescent probes for the analysis of explosives, and specifically, the detection of trinitrotoluene (TNT) or trinitrotriazine (RDX). The QDs are functionalized with electron‐donating ligands that bind nitro‐containing explosives, exhibiting electron‐acceptor properties, to the QD surface, via supramolecular donor–acceptor interactions leading to the quenching of the luminescence of the QDs.